Implementasi Algoritma Genetika Pada Perancangan Aplikasi Android Untuk Memprediksi Buta Warna - Meirina Suci Ridha; Hani Harafani (JURNAL TEKNIK KOMPUTER, 2019)
Color blindness is one of the decreasing diseases which is very difficult to determine its deterioration, whether a family member will suffer from color blindness or not, especially with the prediction of color blindness which has been using manual methods by calculating the inheritance formula. Genetic Algorithms have advantages over other traditional optimization algorithms. To implement a computerized method in predicting color blindness that can be used by many people, it is necessary to have a user-friendly operating system like the Android operating system. The test results show that the implementation of genetic algorithms in applications to predict color blindness produces more optimal predictions and their application to Android makes the application a user friendly application. Keywords: Heredity, Color Blindness, Genetic Algorithms, Android Application, Color Blindness Predictions